2018
DOI: 10.1002/ange.201801650
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective 1,3‐Alkyl Shift in Alkyl Aryl Ethers: Efficient Synthesis of Optically Active 3,3′‐Diaryloxindoles

Abstract: Reported is the first organocatalytic asymmetric 1,3alkyls hift in alkyla ryl ethers for the synthesis of chiral 3,3'diaryloxindoles using ac hiral Brønsted acid catalyst. Preliminary results showed that each enantiomer of the 3,3'-diaryloxindole,a nd ar acemic mixture,s howed different antiproliferative activities against HeLa cell lines by using an MTT assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The route in Scheme 3A yields usable quantities of material; however, inconsistent yields, impurity formation, and multiple batch failures were observed upon scale-up. Taking inspiration from other work on the synthesis of 3,3,-disubstituted oxindoles utilizing heteroatom nucleophiles, 30,31 we found that employing THF as the solvent (step 1, Scheme 3B) yielded a cleaner tertiary chloride intermediate. Changing to a more basic reaction with excess cesium carbonate in dichloromethane with overnight stirring followed by TBAF deprotection was a highly efficient route to compound 2, produced in 95% yield over three steps (Scheme 3B).…”
Section: ■ Resultsmentioning
confidence: 90%
“…The route in Scheme 3A yields usable quantities of material; however, inconsistent yields, impurity formation, and multiple batch failures were observed upon scale-up. Taking inspiration from other work on the synthesis of 3,3,-disubstituted oxindoles utilizing heteroatom nucleophiles, 30,31 we found that employing THF as the solvent (step 1, Scheme 3B) yielded a cleaner tertiary chloride intermediate. Changing to a more basic reaction with excess cesium carbonate in dichloromethane with overnight stirring followed by TBAF deprotection was a highly efficient route to compound 2, produced in 95% yield over three steps (Scheme 3B).…”
Section: ■ Resultsmentioning
confidence: 90%
“…Patil and co-workers expanded an efficient and mild chiral Brønsted acid catalyzed asymmetric 1,3-alkyl shift of alkyl aryl ethers 23. 58 A broad range of substituted enantiomers of 3,3′-diaryloxindoles 24 have been prepared with good to excellent yields (up to 88% yield, 99% ee). As a demonstration of the scalability of this system, this reaction can be readily scaled up to 3 mmol without significant loss of efficiency.…”
Section: Brønsted Acid Catalysismentioning
confidence: 99%
“…Cell growth assays were carried out using MTT (3-(4,5dimethylthiazol-2-yl)-2,5-diph-enyltetrazolium bromide) reagent (Sigma, USA) as described previously [52]. In brief, transfected cells were trypsinized, counted, and plated into 96-well plates.…”
Section: Mtt Assaysmentioning
confidence: 99%